Pengaruh Durasi Penggunaan Gadget terhadap Kejadian Kelainan Refraksi Mahasiswa Universitas Ma Chung Malang - Hendra Yuda; Rachman Irwanto (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Refractive errors occur when the light entering the eye is not clearly focused, causing blurry or unsharp vision. The main causes of refractive errors include hereditary factors and an unhealthy lifestyle. Signs and symptoms of refractive errors include blurred vision, frequent squinting to see objects clearly, and difficulty focusing when reading, watching TV, or looking at a gadget screen. This disorder cannot be completely cured, but it can be helped with glasses, contact lenses, or lasik surgery. The urgency of this research is driven by the increasing duration of gadget use among Ma Chung University students in June 2023 and its impact on eye refractive errors. The purpose of this study is to determine the effect of the duration of gadget use on refractive errors in students. The targeted output is empirical data on the relationship between the duration of gadget use and the incidence of refractive errors, which can be the basis for eye health interventions among students.